1988
DOI: 10.1136/oem.45.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of workers at acetylene production plants.

Abstract: To reduce the risk of explosion oxyacetylene cylinders are filled with a spongy mass, acetone is added to saturate the mass, and acetylene is pumped into the cylinder. The first cylinders manufactured before 1936 By the late 1970s the stock of kapok cylinders was less than 10% of all cylinders in circulation. Kapok cylinders at present account for less than 5% of the total DA cylinder stock.DA cylinders had to be examined by law annually to ensure that the mass was in sound condition. The methods of examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…“Unknown” or “various” exposures indicate the data came from occupational exposure matrices, including textiles, insulation, or cement workers. Sources: a Olsson, 2004. b Gold, 2007. c Greaves, 1979. d Noonan, 2006. e Pfau, 2008. f Gold, 2007; Noonan, 2006. g Rihova, 2005; Inoue, 2004. h Stratta, 2001. i Rihova, 2005. j Inoue, 2004. k Turner-Warwick, 1970. l Zerva, 1989. m Pfau, 2005; Nigam, 1993; Tamura, 1993; Stansfield, 1974. n Pelclova, 2003. o Pfau, 2005. p Pernis, 1965; Turner-Warwick, 1970; Stansfield, 1974; Lange, 1974. q Zone, 1985; Zerva, 1989. r White, 1974. s van Bommel, 2009; Vaglio, 2009; Uibu, 2004; Sauni, 1998; Maguire, 1991. t Cottin, 2008.…”
Section: Autoimmune Effects Of Asbestosmentioning
confidence: 99%
See 1 more Smart Citation
“…“Unknown” or “various” exposures indicate the data came from occupational exposure matrices, including textiles, insulation, or cement workers. Sources: a Olsson, 2004. b Gold, 2007. c Greaves, 1979. d Noonan, 2006. e Pfau, 2008. f Gold, 2007; Noonan, 2006. g Rihova, 2005; Inoue, 2004. h Stratta, 2001. i Rihova, 2005. j Inoue, 2004. k Turner-Warwick, 1970. l Zerva, 1989. m Pfau, 2005; Nigam, 1993; Tamura, 1993; Stansfield, 1974. n Pelclova, 2003. o Pfau, 2005. p Pernis, 1965; Turner-Warwick, 1970; Stansfield, 1974; Lange, 1974. q Zone, 1985; Zerva, 1989. r White, 1974. s van Bommel, 2009; Vaglio, 2009; Uibu, 2004; Sauni, 1998; Maguire, 1991. t Cottin, 2008.…”
Section: Autoimmune Effects Of Asbestosmentioning
confidence: 99%
“…Some of these same studies did show an increase in ANA frequency with asbestos exposure, and despite technical disparities, small study sizes, and limited exposure assessments, the combined strength of these studies is compelling ( Turner-Warwick & Parkes, 1970 ; Stansfield & Edge, 1974 ; Zerva et al, 1989 ; Pfau et al, 2005 ; Tamura et al 1993 ; Nigam et al 1993 ). Only one study indicated no association of positive ANA tests with asbestos exposure, but that study only consisted of 25 asbestos workers ( Zone & Rom, 1985 ), and other immunological indices were positive, such as increased serum IgG/IgA and immune complexes.…”
Section: Autoimmune Effects Of Asbestosmentioning
confidence: 99%
“…Reports of severe burns associated with the use of oxyacetylene are rare, although excess deaths due to cancer associated with asbestos-lined oxyacetylene cylinders have been reported 2. Health and safety regulations concentrate on the necessity for protective eye, face and hand clothing during the use of oxyacetylene welding torches.…”
Section: Introductionmentioning
confidence: 99%